Recognising Women’s Work as Creative Work - Pearlman, Karen; Heftberger, Adelheid (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2018)
The editorial article to the themed issue Women at the Editing Table: Revising Soviet Film History of the 1920s and 1930s (Picture: Leeanna Walsman as Svilova, composing a sequence in 'Woman with an Editing Bench' ©2016 The Physical TV Company)